NILAI MODERASI DALAM RELASI SOSIAL: ANALISIS QS. AL-HUJURAT: 13 DALAM TAFSIR AL-MISHBAH KARYA M. QURAISH SHIHAB - Muhammad Tauhid; Muhammad Akbar Nugraha; Sayyidatina Aisyah; Farkha Fitri Fadilah; Kholil Musthofa; Achmad Rifki Al-farizi; Idam Mugi Salam (Journal Khafi : Journal Of Islamic Studies, 2025)
This study develops the Ta'aruf-Taqwa Operational Model as a prescriptive-operational framework to strengthen social moderation (wasathiyyah) in Indonesia. This model is based on the interpretation of QS. Al-Hujurat: 13 in Tafsir Al-Misbah by M. Quraish Shihab and the context of Indonesia's diversity, which is prone to conflicts based on ethnicity, religion, race, and intergroup relations (SARA). This verse emphasizes human equality and interprets diversity as the basis for mutual understanding (li-ta'arrafu). Quraish Shihab emphasizes that Ta'aruf requires active recognition, flexibility, and compassion as a form of moderation. Meanwhile, Taqwa is the only measure of nobility, as well as a rejection of identity discrimination. The novelty of this research lies in the integration of Ta'aruf as a mechanism of horizontal interaction that encourages social flexibility and Taqwa as a framework of vertical regulation that maintains justice. This model transforms moderation from an ethical concept into concrete practice, with implications for the reform of the Islamic curriculum and the strengthening of the role of scholars in responding to social conflicts.